EEG Maturational Changes in Partial Epilepsies - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1994)
Changes and migration of EEG foci with age in 208 patients with childhood partial epilepsy followed for more than 3 years are reported from the Department of Pediatrics, Toyama Medical and Pharmaceutical University, Toyama City, Japan.